Effect of Negative - Phase Voltage on the MAO Film Properties of 6005A - T6 Aluminum Alloy for City Rail Car Body - PAN Hai - yang, ZHANG Dan - dan, ZHANG En - ping (Cailiao Baohu, 2021)
In order to improve the wear resistance of the surface of 6005A - T6 aluminum alloy for city rail car body, the thin film with high wear resistance was prepared by micro - arc oxidation treatment, and the changes of structure characteristics, hardness and wear resistance of micro - arc oxidation layer caused by negative - phase voltage parameters were analyzed. Results showed that after micro - arc oxidation of the aluminum alloy 6005A - T6, γ - aluminium oxide was formed in the thin film. The formed thin film had an obvious volcanic structure, the overall surface was relatively rough, forming many micron holes with different sizes and a large number of molten particles. The thin film contained the internal dense tissue and the external relatively loose structure, which had a 4 μm dense layer tissue. Micro - arc oxidation increased the hardness of aluminum alloy significantly, and the highest hardness (1 265 HV) was obtained when the negative - phase voltage was at -100 V. When the negative - phase voltage was at -100 V, the friction coefficient was small and relatively stable, showing excellent wear resistance. Besides, the MAO thin film presented the appearance of white strips, and some black lumpy tissues were also observed. Under the condition of -100 V, smaller lumpy areas were formed in the prepared sample.